The Effect of Using Audiobook Media on EFL Students Listening Skill - M. Iqbal Kharis Mawardi; Nuri Ati Ningsih; Rizqi Husaini (Universitas PGRI Madiun, 2025)
Listening is a language skill that takes a bigger part in daily communication along with speaking, reading and writing. This is because, listening is considered as one of the important skills to achieve effective communication. this study aims to know the use of audiobook media to teach listening skill by EFL student. The method use of this research is using qualitative method with questionary form that must fill by the respondent. The result of this research present that all the respondents said that the effect of using audiobook media is good for student because it can improve some aspect of students listening skill. So, it concludes that the audiobook media can be use as teaching media to teach listening skill because within this media can improve student ability in listening and can improve of the other aspect.